2023
DOI: 10.3390/antiox12071380
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α-Amylase, α-Glucosidase, Pancreatic Lipase, 15-Lipooxygenase and Acetylcholinesterase Modulated by Polyphenolic Compounds, Organic Acids, and Carbohydrates of Prunus domestica Fruit

Abstract: This work aimed to establish the content of phenolic compounds, carbohydrates, and organic acids and to determine their potential to inactivate α-amylase, α-glucosidase, pancreatic lipase, 15-lipoxygenase (15-LOX), acetylcholinesterase (AChE), and butyrylcholinesterase (BuChE), and antioxidant activity (ABTSo+ and FRAP) in 43 Prunus domestica cultivars. We identified 20 phenolic compounds, including, in the order of abundance, polymeric procyanidins, flavan-3-ols, phenolic acids, flavonols, and anthocyanins. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Bioactive compounds such as anthocyanin and TPC enhance food quality, such as color and taste, and play an essential role in human wellness [66]. Anthocyanins are provided in purple, blue, or red colors for fruit [67]. The results revealed that the TAC content was significantly (p < 0.05) decreased to 3.45 mg/100 mL compared to 4.29 mg/100 mL after 24 months of storage.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Bioactive compounds such as anthocyanin and TPC enhance food quality, such as color and taste, and play an essential role in human wellness [66]. Anthocyanins are provided in purple, blue, or red colors for fruit [67]. The results revealed that the TAC content was significantly (p < 0.05) decreased to 3.45 mg/100 mL compared to 4.29 mg/100 mL after 24 months of storage.…”
Section: Bioactive Compoundsmentioning
confidence: 99%